Test-retest reliability, validity, and minimum detectable change of visual analog, numerical rating, and verbal rating scales for measurement of osteoarthritic knee pain - Alghadir, Ahmad; Anwer, Shahnawaz; Iqbal, Amir; Iqbal, Zaheen (Journal of pain research, 2018)
Several scales are commonly used for assessing pain intensity. Among them, the numerical rating scale (NRS), visual analog scale (VAS), and verbal rating scale (VRS) are often used in clinical practice. However, no study has performed psychometric analyses of their reliability and validity in the measurement of osteoarthritic (OA) pain. Therefore, the present study examined the test-retest reliability, validity, and minimum detectable change (MDC) of the VAS, NRS, and VRS for the measurement of OA knee pain. In addition, the correlations of VAS, NRS, and VRS with demographic variables were evaluated. The study included 121 subjects (65 women, 56 men; aged 40-80 years) with OA of the knee. Test-retest reliability of the VAS, NRS, and VRS was assessed during two consecutive visits in a 24 h interval. The validity was tested using Pearson's correlation coefficients between the baseline scores of VAS, NRS, and VRS and the demographic variables (age, body mass index [BMI], sex, and OA grade). The standard error of measurement (SEM) and the MDC were calculated to assess statistically meaningful changes. The intraclass correlation coefficients of the VAS, NRS, and VRS were 0.97, 0.95, and 0.93, respectively. VAS, NRS, and VRS were significantly related to demographic variables (age, BMI, sex, and OA grade). The SEM of VAS, NRS, and VRS was 0.03, 0.48, and 0.21, respectively. The MDC of VAS, NRS, and VRS was 0.08, 1.33, and 0.58, respectively. All the three scales had excellent test-retest reliability. However, the VAS was the most reliable, with the smallest errors in the measurement of OA knee pain.